European Financial Reporting: 4 The Netherlands (Book). - Choi, Frederick D.S.; Burns, Thomas J. (The Accounting Review, 1980)
Reviews the book "European Financial Reporting: The Netherlands," by J.H. Beeny and J.G. Chastney.